Degradation mechanisms effect on the mechanical properties of pultruded CFRPS: a review - Chaffey, Brace; Marchante Rodriguez, Veronica; Brighton, James L.; Grasso, Marzio (Springer, 2025)
Environmental factors such as ultraviolet (UV) radiation, moisture, and temperature can promote degradation mechanisms in pultruded carbon fibre composites. It has been shown that UV radiation coupled with moisture accelerates chemical reactions, leading to molecular bond breakage and chalking, compromising the surface and the matrix. UV radiation and temperature have been shown to significantly impact durability when combined with mechanical loading. While some studies have provided valuable insights into the single degradation processes associated with UV radiation, moisture, and mechanical loading, a comprehensive understanding of their concurrent effects, particularly under conditions representative of open-field exposure, remains limited. This gap is largely attributed to key limitations in the existing body of research, including over generalised experimental protocols, a lack of standardised test methods for any simultaneous application, wide variability in material compositions and a predominant focus on single or sequential rather than simultaneous exposure scenarios. This review covers degradation mechanisms due to single, sequential and combined environmental effects with related testing approaches used to predict residual life. This review emphasises the need for a deeper understanding of the synergistic effects in the design and application of pultruded CFRP composite and for more realistic environmental conditions during testing to mimic real-world scenarios. In particular, the inclusion of mechanical loading within environmental chambers is essential for capturing the interactive effects of simultaneous environmental and mechanical stress.
Keywords: 40 Engineering; 4016 Materials Engineering; Climate-Related Exposures and Conditions; Generic health relevance; CFRP; Pultrusion; Accelerated ageing; UV; Moisture